HUBUNGAN ANTARA KEYAKINAN MATEMATIS DAN HASIL BELAJAR SISWA KELAS VIII MTS DARUL ULUM - Abdul Aziz; Agung Hartoyo; Romal Ijuddin (Universitas Tanjungpura, 2021)
AbstractThe aim of the research is to find the relationship between mathematical beliefs and learning outcomes. This research uses ex post facto method and correlational research form. The samples in the study were students of class VIII A, the data obtained in the study were the results of a questionnaire on mathematical beliefs and the value of learning outcomes. Based on the results of the research, it was found that 0.594 showed a relationship between mathematical beliefs and learning outcomes and was in the moderate category. So it can be concluded that if mathematical confidence is high, learning outcomes are also high. Keywords : Mathematical belief, Learning outcomes